1997
DOI: 10.1051/aas:1997143
|View full text |Cite
|
Sign up to set email alerts
|

A photometric catalogue of the Coma cluster core

Abstract: Abstract. We have obtained a mosaic of CCD images of the Coma cluster in the V -band covering a region of approximately 0.4 degrees 2 around both central cluster galaxies NGC 4889 and NGC 4874. An additional frame of ∼ 90 arcmin 2 was taken of the south-west region around NGC 4839. We derived a catalogue of 7023 galaxies and 4096 stars containing positions, central surface brightnesses and isophotal V 26.5 magnitudes. We estimate that data is complete up to V 26.5 ∼ 22.5 and the surface brightness limiting det… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 2 publications
7
54
0
Order By: Relevance
“…The works that have studied the segregation in luminosity present some contradictory results. Rood & Turnrose (1968), Yepes et al (1991), Lobo et al (1997), Kashikawa et al (1998), Coenda et al (2006) found results consistent with a segregation in luminosity. Nevertheless, Noonan (1961), Bahcall (1973) and more recently Pracy et al (2005) found results consistent with a lack of segregation in luminosity.…”
Section: Introductionsupporting
confidence: 54%
“…The works that have studied the segregation in luminosity present some contradictory results. Rood & Turnrose (1968), Yepes et al (1991), Lobo et al (1997), Kashikawa et al (1998), Coenda et al (2006) found results consistent with a segregation in luminosity. Nevertheless, Noonan (1961), Bahcall (1973) and more recently Pracy et al (2005) found results consistent with a lack of segregation in luminosity.…”
Section: Introductionsupporting
confidence: 54%
“…Galaxies brighter than M R = −22.8 are mostly BCGs, and have been mostly excluded from our samples by removing the very central cluster regions, R n < 0.05. While there are several indications that dwarf galaxies in clusters have a different phase-space distribution from bright galaxies (e.g., Lobo et al 1997;Kambas et al 2000;Odell et al 2002;Popesso et al 2006), this is irrelevant here since dwarf galaxies are not present in our samples.…”
Section: The Construction Of the Stacked Cluster Samplesmentioning
confidence: 93%
“…Evidence of a steep LF of field galaxies at infrared wavelength come from Szokoly et al (1998) who find a slope α = −1.3 and from Bershady et al (1999) who estimate α = −1.6. Other evidence in favor of α −1 come from the results obtained on optically selected samples of field galaxies (Marzke et al 1994(Marzke et al , 1997Zucca et al 1997) and of cluster galaxies (De Propris et al 1998;Lobo et al 1997;Bernstein et al 1995;Molinari et al 1998). However, such a steep LF, which contributes substantially to the galaxy counts at optical wavelengths (see e.g.…”
Section: Comparison With Modelsmentioning
confidence: 97%